AN ANALYSIS OF MAQĀṢID AL-SHARĪʿAH IN THE PRACTICE OF ANGKAP MARRIAGE AMONG THE GAYO ETHNIC GROUP - Muhammad Haris, Rizki; Nasution, Muhammad Iqbal Hanafi (El-Ahli : Jurnal Hukum Keluarga Islam, 2025)
This study aims to examine the practice of angkap marriage in the Gayo traditional community through the Maqashid Syariah perspective, especially in the aspect of safeguarding property (hifzh al-mal). angkap marriage is a form of social adaptation that arises as a solution to the problem of the absence of sons in a family, as well as the economic obstacles experienced by the male party in carrying out marriage, especially in terms of fulfilling the dowry or edet. This research uses a normative juridical method with a statute approach, namely by analyzing written legal norms and related maqashid sharia principles. The analysis technique used is qualitative. The results show that angkap marriage provides a practical solution in maintaining the continuity of family property through the appointment of a son-in-law as part of his wife's family. The implication is that the husband changes his position in the inheritance system and becomes the protector of his in-laws' property. This tradition does not substantially contradict Islamic law and instead reflects the objectives of Islamic law, namely maintaining benefits, strengthening family resilience, and keeping property in a safe and reliable environment.